The Paradox of Empowerment: A SEM-Based Study on How Job Satisfaction Mediates Empowerment and Quit Intention (The Lumbini Journal of Business and Economics, 2026)
Purpose: Globally, employees’ sustainability and retention of competitive manpower are major issues across industries. The paper aims to examine the impacts of empowering employees, both direct and indirect, on the intention of banking staff in Nepalese A-class banks to quit their jobs.Methods: A systematic survey grounded in questionnaires is applied to gather firsthand information from 483 purposefully selected banking staff. SEM was applied to investigate the projected hypothesis and model.Results: SEM revealed powerful repercussions of employee empowerment indirectly on intention to quit jobs through job satisfaction, but showed an insignificant direct impact on quitting intention. It exposed that job satisfaction fully mediates the link between empowering employees and their job quitting intentions. Conclusion: It concludes that, psychologically empowered workers are more likely to receive favorable performance evaluations and be reluctant to quit jobs they enjoy, thereby reducing the desire to quit. Further, for gaining more insights a longitudinal data and mixed-method approach may also be taken into consideration. Concerned bank authorities may find the information of this paper useful in formulating strategic choices on employee empowerment. Study outcomes align with the social exchange theory.